2016
DOI: 10.1177/0309816816667424
|View full text |Cite
|
Sign up to set email alerts
|

Destroy what destroys the planet: Steering creative destruction in the dual crisis

Abstract: In the contemporary dual crisis, economic crisis policies cannot be dealt with in isolation from the rampant and acute ecological crisis – and vice versa. In this article, we challenge the hegemonic positions in purported attempts to solve the crises so far: in the economic realm, the Keynesian episode of 2008–2009 as well as austerity policies, and with regard to the ecological crisis, ecological modernization and green economy. Instead, we will propose that both the economic and the climate crises can be ‘so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 50 publications
0
10
0
Order By: Relevance
“…Concerning our third component—the diabolic crisis—more analytical work is needed. But a Marxist theoretical approach, I argue, does give a more profound understanding of both crises than any other economic theory: locating the ultimate causes of crises in economic growth (crucial for ecological crisis) and contradictions within capital accumulation (as in economic crisis), as well as revealing the relations between these crises, and how crises normally are solved (through creative destruction) (Holgersen and Warlenius ; Næss , ).…”
Section: Towards Marxist Planning: the Dialectics Of Is And Oughtmentioning
confidence: 99%
See 2 more Smart Citations
“…Concerning our third component—the diabolic crisis—more analytical work is needed. But a Marxist theoretical approach, I argue, does give a more profound understanding of both crises than any other economic theory: locating the ultimate causes of crises in economic growth (crucial for ecological crisis) and contradictions within capital accumulation (as in economic crisis), as well as revealing the relations between these crises, and how crises normally are solved (through creative destruction) (Holgersen and Warlenius ; Næss , ).…”
Section: Towards Marxist Planning: the Dialectics Of Is And Oughtmentioning
confidence: 99%
“…This means that they should encompass both ecological and economic perspectives, but also contain both creative and destructive components. It is not only enough to plan more environmentally friendly buildings and infrastructure; we also need to actively devalue the landscapes of fossil capital (Holgersen and Warlenius ). Radical programmes should seek to introduce Marxist creative destruction.…”
Section: Towards Marxist Planning: the Dialectics Of Is And Oughtmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have shown that new investments in renewable energy in fact add to existing production, instead of replacing it (York 2012). Another is the Jevons paradox: where new and improved technology can contribute to both increased profits and overall growth, and thus increased emissions (Foster et al 2010, Holgersen andWarlenius 2016). Despite key differences, the solutions posed by both austerity (through green fixes) and Keynesianism (through green new deals) to the diabolic crisis are underpinned by ecological modernism, an ideology claiming that more economic growth and more affluence is the remedy to the ecological crisis (Foster et al 2010, Foster and Burkett 2016, Malm 2016.…”
Section: Climate Change and Technologymentioning
confidence: 99%
“…6 Halpern and Mitchell 2011. 7 Hart and Milstein 1999;Hart 2005;Hartshorn et al 2005;Holgersen and Warlenius 2016. scholarship beyond the heritage field, this exploration does not delve into the theoretical debates about authenticity and physical reconstruction that are well represented in the heritage canon. Rather, it is premised on a recognition of heritage being fundamentally a social reconstruction of built assets, a process that is not politically neutral.…”
mentioning
confidence: 99%